Nuevo registro de clinopodium Weberbaueri (Mansf.) Grovaerts “runtuwayra” para la provincia de Andahuaylas. Perú - Sotelo Cañari, María del Carmen (2014)
A new record of Clinopodium weberbaueri (Mansf.) Grovaerts “runtuwayra” specimens for the Andahuaylas Province of Peru are registered and presented. These specimens were collected in the Distrito of Pacucha, Provincia of Andahuaylas (2926 m.s.n.m.), Apurímac region (2900 m.s.n.m.). Previews records of this specie in this area no were reported, so these specimens expands the knowledge about its geographical distribution of this specie into the Peruvian southern Andean area.